Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025631
|View full text |Cite
|
Sign up to set email alerts
|

PersaLog

Abstract: Content personalization-automatically modifying text and multimedia features within articles based on the reader's individual features-is evolving as a new form of journalism. Informed by constraints articulated through a survey of journalists, we have implemented PersaLog, a novel system for creating personalized content (e.g., text and interactive visualizations). Because crafting, and validating, personalized content can be challenging to scale across articles (unlike feed personalization), we offer a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…There is a rich literature on adaptive interfaces and personalization in many domains, including website design [86], advertisement [46,101], study recruitment [8], journalism [2], and education [35,38,77]. Usually personalization focuses on adjusting visual elements, but work has also shown the benefit of adjusting language to different audiences.…”
Section: Personalizing Languagementioning
confidence: 99%
See 2 more Smart Citations
“…There is a rich literature on adaptive interfaces and personalization in many domains, including website design [86], advertisement [46,101], study recruitment [8], journalism [2], and education [35,38,77]. Usually personalization focuses on adjusting visual elements, but work has also shown the benefit of adjusting language to different audiences.…”
Section: Personalizing Languagementioning
confidence: 99%
“…Prior work has found that such tailoring of patient pamphlets can improve health outcomes, including smoking behavior and future health complications [66,96,100]. In journalism, Adar et al [2] introduced PersaLog, a system for authoring personalized news articles. Articles authored using PersaLog presented alternative content (e.g., heat estimates for different areas) depending on user traits (e.g., a user's location).…”
Section: Personalizing Languagementioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Smith and Linden (2017) showed that filtering algorithms capable collect, sort and prioritize data about the users' behavior [60]. In 2017, some scholars conducted a study entitled: PersaLog: Personalization of News Article Contentthey introduced the PersaLog system for journalism professionals which able to content personalization, as well as enhance learning and behavioral changes in readers and increase engagement [61]. In sum, news sites today can be offering everything most users need by using "cookies", such as personalized content by register different information from real uses of users while they act on the given website [62].…”
Section: Content Personalizationmentioning
confidence: 99%
“…capabilities, LLMs have the potential to change creative language arts (CLA) 1 . New LLM-based tools can provide authors with AIgenerated suggestions based on the author's own writing or instructions [18,58].…”
mentioning
confidence: 99%